2008
DOI: 10.1073/pnas.0804900105
|View full text |Cite
|
Sign up to set email alerts
|

Metal-organic frameworks with high capacity and selectivity for harmful gases

Abstract: Benchmarks have been established for the performance of six metal-organic frameworks (MOFs) and isoreticular MOFs (IRMOFs, which have the same underlying topology as MOF-5), MOF-5, IRMOF-3, MOF-74, MOF-177, MOF-199, and IRMOF-62, as selective adsorbents for eight harmful gases: sulfur dioxide, ammonia, chlorine, tetrahydrothiophene, benzene, dichloromethane, ethylene oxide, and carbon monoxide. Kinetic breakthrough measurements are used to determine the calculated dynamic adsorption capacity of each ''benchmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
600
4
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 869 publications
(626 citation statements)
references
References 24 publications
19
600
4
3
Order By: Relevance
“…[19][20][21] During recent years it has been shown that a large variety of 2-D and 3-D metal organic networks with high porosity, unusual ions exchange and adsorptive properties can be designed using intermolecular interactions and metal-ligand coordination. [22][23][24][25] The structure of the materials obtained is the result of maximum degrees of freedom of both components, spherical shape of metal ions and welldefined points of contacts in the organic linkers. [26] In spite of the very high porosities of MOFs, their open framework is not able to provide strong nonspecific adsorption forces to retain small molecules at ambient conditions.…”
Section: Another Group Of Materials Which Has Recently Open New Possimentioning
confidence: 99%
“…[19][20][21] During recent years it has been shown that a large variety of 2-D and 3-D metal organic networks with high porosity, unusual ions exchange and adsorptive properties can be designed using intermolecular interactions and metal-ligand coordination. [22][23][24][25] The structure of the materials obtained is the result of maximum degrees of freedom of both components, spherical shape of metal ions and welldefined points of contacts in the organic linkers. [26] In spite of the very high porosities of MOFs, their open framework is not able to provide strong nonspecific adsorption forces to retain small molecules at ambient conditions.…”
Section: Another Group Of Materials Which Has Recently Open New Possimentioning
confidence: 99%
“…1) (9). This material was found to have exceptional separation capacity for gases such as sulfur dioxide, ammonia, and ethylene oxide (10), and H 2 storage capacity (11). Subsequent to this initial discovery, a series of MOFs in which the 5-coordinate zinc(II) ions of MOF-74 are substituted for various divalent metal ions, including nickel, cobalt, manganese, and magnesium, has been described in various reports (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…27 The breakthrough time is defined as the time when the outlet concentration was about 5% of the inlet concentration. 28 The adsorbed amounts were calculated by the equation…”
Section: Adsorption Measurementsmentioning
confidence: 99%